Datos KT escuela de Tri. - Merino-Marban, Rafael; Fernández-Rodríguez, Emilio; Mayorga-Vega, Daniel (Universidad de Málaga, 2024)
The purpose of the present study was to examine the effect of KT on 30 m sprint and counter movement jump performance in active children. Methods. A randomized crossover, pretest/posttest repeated measures design was used to compare the effects of KT on triceps surae and no taping. To generate the random assignment sequence, the data collection sheets were randomly marked with a small letter a or b alternatively. Only the KT practitioner knew that these letters corresponded to one of the two groups. The two sessions were separated for three days to avoid accumulation of the KT effects and took place on the same public sports track. Of the 28 healthy active children (12 girls and 16 boys) enrolled in a triathlon school, all children voluntarily participated in the present study. Results. The results of the ANOVA on the average obtained in the counter movement jump test showed differences statistical significant a favor of KT condition [F(1, 19) = 12.383, p = 0.002; η2 = 0.395; P = 0.916]. However, the ANOVA results on the average obtained in the sprint test did not show differences statistical significant in 0-15 m, 15-30 m, and 0-30 m. Conclusions. KT on the triceps surae does not seem to affect the sprint performance in apparently healthy active children, but it does on the counter movement jump test. The KT application did not cause any discomfort or injury to the children during the study.
Keywords: Kinesiología; I technique; Calf muscles; Triceps surae; 30-m running sprint test; Jump